Barikan Tradition as A Form of Local Wisdom Preservation In Kebonadem Village - Muamanah Tri Wiyanto; Siti Riaddhotul Jannah; Nurul Azizah; Ahmad Rudi; Muhammad Bahrudin Al Anshory; Dwi Hartanti (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
This research aims to analyze and document the barikan tradition in Kebonadem Village as a form of preserving local wisdom which has social, spiritual and educational values. The problem faced is the decreasing interest of the younger generation in preserving this tradition amidst the strong current of modernization. This raises concerns that this tradition, which has been passed down from generation to generation, will be eroded by more popular foreign culture. The urgency of this research lies in the importance of understanding and maintaining the values contained in the Barikan tradition so that it remains relevant and can be passed on to future generations. The research results show that the Barikan tradition not only functions as an annual ritual, but also as a tool to strengthen social ties and deepen people's faith, especially in teaching children the values of togetherness, mutual help and respect for tradition. This tradition, despite facing the challenges of modernization, remains an integral part of the life of the people of Kebonadem Village, connecting the past, present and future, and enriching local cultural identity.